Effect of tris(catecholato) silicate (TCS) ion concentration in silica carrier microencapsulation (SCME) treatment of Toledo pyrite concentrate for the suppression of pyrite oxidation - Capistrano, Milbert M.; Cayaban, Lorenzo T.; Lopez, Joshua Miguel D.; Calaywan, Juan Fidel B.; Palmejar, Russell Roy (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
Acid mine drainage is produced when pyrite interacts with water and oxygen. This study investigates the suppression of pyrite oxidation by silica carrier microencapsulation technique (SCME). In SCME, catechol (C₆H₆O₂) was used as an organic carrier to introduce silica particles on to the surface of pyrite particles, foming a protective coating. To test the suppression of pyrite oxidation, accelerated weathering was performed to 20 g pyrite treated with 0 mM, 0.5 mM, 1 mM, 5 mM, 10 mM and 50 mM tris (catecholato) silicate (TCS) solution. The parameters observed were pH and electrical conductivity over a period of 5 days and the final Fe concentration. Statistical analysis of pH, EC and Fe concentration using one-way ANOVA with blocking and Dunnett's t-test showed that differences between the control, 0.5 mM, and 1 mM treatments are found to be insignificant: 5 mM, 10 mM, and 50 mM treatments has a direct correlation between pH and TCS concentration, and inverse correlations between EC and Fe concentration, and TCS concentration. SEM-EDX analysis also shows buildup of silica on pyrite surface. It can be concluded that SCME at 5, 10 and 50 mM treatments reduced pyrite oxidation of a 20g pyrite sample.
Thesis (B.S. Mining Engineering)--University of the Philippines Diliman
Keywords: Acid mine drainage; Pyrites -- Oxidation; Microencapsulation